Performance of Space-Frequency-Time Coded OFDM Systems with Transmit Antenna Selection in Land Mobile Satellite Channel - Cinar, Cihat; Kavas, Aktuel (IEEE, 2009)
In this work, land mobile satellite (LMS) communications, transmit antenna selection (TAS) method is applied to space-frequency-time coded orthogonal frequency division multiplexing (SFT Coded OFDM) with Alamouti and trellis coded over satellite channel of Loo's model with 2 multipath, equal power profile and 8 multipath, exponential power profile frequency selective, quasi-static Rayleigh fading and the systems are compared in terms of the frame error rate performance. For land mobile satellite channel, high diversity gains are obtained without changing the current system complexity and current number of transmitting antenna simultaneously. As the number of transmit antennas increase the gain increases too.
Keywords: Computer Science; Engineering; Telecommunications